Assessment of the Resistance of Dolomite Stone from Crac des Chevaliers Against Salt Crystallization - Bilal, Ola; Rozgonyi-Boissinot, Nikoletta (Periodica Polytechnica Civil Engineering, 2023)
This study was dedicated to evaluating the durability of the carbonatic stones of Crac des Chevaliers castle against salt crystallization. Crac des Chevaliers castle is a UNESCO world heritage site located in Syria and is considered one of the most important crusader castles built in the 12th century. Salt efflorescence is a common decay type detected on the stone blocks of this building, so six dolomite stone lithotypes with various structures tested under salt aging in three different salt solutions; sodium chloride, magnesium sulfate, and sodium sulfate. Among those lithotypes were two microbioclastic wackstone and four microcrystalline dolomite. The microbioclastic wackstone had low open porosity (18 and 11 v/v%) compared to the microcrystalline dolomites of about 28v/v% open porosity. Two of the microcrystalline dolomite lithotypes had bimodal pore networks and around 4 v/v% closed pores, however, the other two exhibited very small closed porosity (around 0.35 v/v%). The results revealed that even though the great effect of the open porosity on the durability of the specimens, the closed porosity also had a major role and the weathering form depended on the salt composition and the stone porosity properties. The primary decay type of the specimens in sodium sulfate solution was granular disintegration while pitted surfaces formed in sodium chloride solution, and the exfoliation of the stone surface into thin layers was observable after the aging with magnesium sulfate solution. The effect of NaCl crystallization on the specimen was not as aggressive as that of the sulfates.